2020
DOI: 10.1186/s12906-020-02905-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of cardiovascular protective effect of Shenmai injection by network pharmacology and pharmacological evaluation

Abstract: Background: Shenmai injection (SMI) has been used in the treatment of cardiovascular disease (CVD), such as heart failure, myocardial ischemia and coronary heart disease. It has been found to have efficacy on doxorubicin (DOX)induced cardiomyopathy. The aims of this study were to explore the underlying molecular mechanisms of SMI treatment on CVD by using network pharmacology and its protective effect on DOX-induced cardiotoxicity by in vitro and in vivo experiment based on network pharmacology prediction.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…When used in combination with chemotherapy drugs, it has a synergistic effect and can reduce the side effects of chemotherapy drugs [ 59 ]. The main components of Shenmai injection are saponins, sugars, amino acids, flavonoids, lignans, organic acids, and other substances [ 60 ]. Shenmai can reduce the level of inflammatory factors, increase anti-inflammatory factors, and reduce the content of white blood cells, c-reactive protein, and procalcitonin when used for the adjuvant treatment of severe pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…When used in combination with chemotherapy drugs, it has a synergistic effect and can reduce the side effects of chemotherapy drugs [ 59 ]. The main components of Shenmai injection are saponins, sugars, amino acids, flavonoids, lignans, organic acids, and other substances [ 60 ]. Shenmai can reduce the level of inflammatory factors, increase anti-inflammatory factors, and reduce the content of white blood cells, c-reactive protein, and procalcitonin when used for the adjuvant treatment of severe pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional Chinese medicine has unique advantages in regulating oxidative stress and cell injury. Shenmai injections are a commonly used drug for myocardial protection in clinics, with confirmed efficacy [ 27 ]. Many studies have shown that Shenmai injection can alleviate myocardial cell damage caused by many factors, including ischemia-reperfusion, doxorubicin, and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…e heart was examined in the long-axis view at the papillary muscle level, and an M-mode echocardiogram of the mid ventricle was recorded. Cardiac function indices including LVEF, LVFS, LVIDd, and LVIDs were recorded [16]. Evidence-Based Complementary and Alternative Medicine 2.4.…”
Section: Ultrasound Echocardiographymentioning
confidence: 99%